Mixed Methods Research Approach: An Overview - Josephine Oranga; Audrey Matere; Evelyn Njurai (Проблеми на постмодерността)
Mixed methods research involves using both quantitative and qualitative methodologies in a single study or inquiry to gain a more comprehensive understanding of the issue under investigation. The methodology draws from the potential strengths of both the quantitative and qualitative methodologies, allowing researchers to explore diverse views and unearth relationships that abound in the intricate layers of multifaceted research questions.  This paper, thus, provides the rationale and philosophical underpinnings of the mixed methods approach while also discussing the paradigms (positivistic/interpretivist/constructivist) from which the mixed methods approach is drawn. Consequently, the main advantages of the mixed methods approach are discussed, these include that the approach enables the research questions to be answered in breadth and depth, helps test validity by converging information from different research methods, transcends the limitations of exclusive quantitative and qualitative research methodologies, responds to questions that either qualitative or quantitative methodologies cannot answer alone. Furthermore, mixed methods research fosters and enriches researchers’ experiences and enables the exploration of diverse perspectives while also revealing the relationships between different layers of phenomena. This article further highlights the limitations of the mixed methods approach, which are measly compared to its pros. Thus, the limitations are: the need for more time and finances to undertake and accomplish the research, increased research workload, and the need for expert involvement at some or all phases of the research. Undoubtedly, the advantages of the mixed-methods approach far outweigh its limitations, hence, it is concluded that the mixed-methods design provides the best chance of responding to research questions exhaustively by its ability to combine two sets of approaches while, at the same time, making up for the weaknesses of each method.